Nitrogen Use Efficiency and Gaseous Nitrogen Losses from the Concentrated Liquid Fraction of Pig Slurries - G. L. Velthof; R. P. J. J. Rietra (International Journal of Agronomy)
Processed manure can be an alternative source of nutrients for untreated manure and mineral fertilizers. Mineral concentrates (MCs) are derived from reversed osmosis of the liquid fraction of separated pig slurries. The emissions of ammonia (NH3) and nitrous oxide (N2O) from different (processed) manures and fertilizers were tested in an incubation experiment and a greenhouse experiment with grass as a test crop. Dry matter yields and nitrogen (N) uptake were also determined in the greenhouse experiment. Incorporation into the soil decreased on NH3 emission but increased N2O emission for all nitrogen products (mineral fertilizer, untreated slurry, MC, and solid fraction of separated slurry). Incorporation of both MC, slurries, and mineral fertilizers increased N2O emission in the incubation experiment. The lowest apparent N recovery (ANR) in the pot experiment with grass was obtained for incorporated pig slurry (30–39%) and surface-applied MC (33–38%), while the highest ANRs were obtained for liquid ammonium nitrate (45–53%) and acidified MC (43–55%). It is concluded that MCs have a similar N fertilizer value as mineral N fertilizers if NH3 emission is reduced by incorporation or acidification.